Assessment of Need for Recovery and Its Relationship With Work Characteristics and Health in a Sample of Chinese Doctors: A Cross-Sectional Survey - Sun, Tao; Shi, Yu; Yin, Dong; Zhang, Shu'e; Wang, Xiaohe (Frontiers in Public Health, 2021)
Background: China is launching an unprecedented health care system reform. However, the long-term interests of doctors seem to have been ignored during this process especially considering that the work environment and work-life balance for doctors have severely deteriorated over the past decade.Their well-being and health are facing substantial threats due to heavy workloads and inadequate recovery opportunities. This study aimed to investigate the extent of need for recovery (NFR) among Chinese doctors and to examine their work-related fatigue. The study also examines the relationship of NFR with workplace satisfaction and health outcomes among Chinese doctors. Methods: A total of 2,617 doctors from 30 administrative regions in China participated in this study to assess the need for recovery and its relationship with work characteristics and health. A cross-sectional survey was conducted using the Chinese version of the Need for Recovery Scale (NFRS). Participants were invited to complete an anonymous online survey during May 2016. Data were analyzed using descriptive statistics, one-way ANOVA, reliability analysis, Pearson correlations, and hierarchical multiple regression analysis. Results: Significant differences in NFR scores were found across demographic characteristics such as age, service years, hospital levels, educational attainment, professional positions, work shifts, and working time. Regardless of any illnesses they might be experiencing, about 70.0% of participants remained at their job even though many doctors (22.1%) must continue working under the policies of the organization, which led to more pronounced NFR (P < 0.001). Further, a higher NFR was negatively related to workplace well-being and self-reported health outcomes of participants. Conclusions: Work-induced fatigue is a growing threat to doctors in China and their recovery opportunities are extremely limited in the workplace. High NFR exerts a considerable effect on their workplace well-being and health. China's hospital managers should pay close attention to the fact that doctors have little chance of recovery, and should offer doctors' positive encouragement and support to enhance well-being. To improve doctors' working conditions, targeted prevention policies must be introduced by policymakers to control this spreading crisis.